Meningkatkan Hasil Belajar Membaca Pemahaman Siswa Pada Pelajaran Bahasa Indonesia Di Kelas IX-2 Melalui Metode Membaca Search, Question, Read, Recite, Record And Review (SQ4R) Di SMP Negeri 2 Tanjung Morawa Pada Tahun Pelajaran 2018/2019 - Herlina Indrawaty (Ability: Journal of Education and Social Analysis, 2022)
The purpose of this research is to: (1). Improving students' reading comprehension learning outcomes, (2). Increase student learning activities. (3). Improve student understanding and learning using the Search, question, read, recite, record and review reading method. The method used in this research is the Classroom Action Research Method using 2 cycles. The subjects of this study were 32 students of SMP Negeri 2 Tanjung Morawa IX-2. The instruments used to obtain data are tests, questionnaires and observations. The data analysis technique used is the assessment method, namely: the data obtained is evaluated based on the results of learning to read students' understanding. Evaluation of students' reading comprehension learning outcomes is given a range of values ??from 0 – 100. Then the data is calculated from the average student score, the percentage of students who have completed and the percentage of students who have not completed meeting the minimum completeness criteria. The results of this study indicate that there is an increase in learning outcomes for reading comprehension by applying the Search, question, read, recite, record and review reading method with the following results: (1) there is an increase in the average learning outcomes for students' reading comprehension, where in the initial test the average the average student reading comprehension result was 45.94, in cycle I it increased to 63.13% then in cycle II it increased again to 65.31%, there was an increase in the number of students who passed, where in the initial test the number of students who passed was only 0% , increased to 56.25% in cycle I then increased again to 81.25% in cycle II, there was a decrease in the number of students who did not complete, where in the initial test the number of students who did not complete reached 100%, in cycle I it became 43.75 % then in cycle II it decreased again to 18.75% in other words only 6 students got a score of 60 and the rest (26) students got a score of 70 and above 70. Application of the sea reading method rch, question, read, recite, record and review can improve students' reading comprehension learning outcomes.